What explains aggregate telecom investments? Evidence from an EU-OECD panel - Klaus S. Friesenbichler (Austrian Institute of Economic Research (WIFO), 2019)
This paper analyses the determinants of aggregate per-capita investments into the telecom sector. We provide results of panel econometric estimates for EU and OECD countries covering the period from 2005 to 2013. The findings show a positive effect of infrastructure-based competition between xDSL broadband and cable-TV broadband subscriptions on investments. We use cross-country variance in open access regulations to examine their effect on investments and find a negative effect for bitstream regulations. The regression results are used to assess the magnitude of these factors, thereby providing valuable inputs to the policy debate on broadband promotion.
Keywords: L38; L43; L52; 330; investment; competition; platform; ladder; unbundling; bitstream; regulation; broadband; telecom